2007
DOI: 10.2220/biomedres.28.9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 2-methoxyestradiol on cell morphology and Cdc2 Kinase activity in WHCO3 esophageal carcinoma cells

Abstract: The influence of 1 × 10 −6 M exogenous 2-methoxyestradiol (2ME) was investigated on nuclear and cytoplasmic morphology, as well as Cdc (cell division cycle) 2 kinase activity in WHCO3 esophageal carcinoma cells. Mitotic indices after 18 h of 2ME exposure revealed an increase in metaphase cells (9.0%) when compared to the vehicle-treated cells (0.9%). 2ME-treated cells showed apoptotic cells at 5.6% after 18 h of exposure to dimethyl sulphoxide, compared to 0.9% in vehicle-treated cells. Increased morphological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The GI 50 concentrations for the compounds are summarized in Table 1. In in vitro studies conducted in our laboratory, 2-ME showed an antiproliferative effect on HeLa, SNO, MCF-7, and MCF-12A cells in a concentration range of 1-2lM (43)(44)(45). Accordingly, Edsall et al (2004) demonstrated that the same compound inhibited MDA-MB-231 cancer cell proliferation by 50% at 1 lM (30).…”
Section: Docking Results: Caii Versus Caixmentioning
confidence: 99%
“…The GI 50 concentrations for the compounds are summarized in Table 1. In in vitro studies conducted in our laboratory, 2-ME showed an antiproliferative effect on HeLa, SNO, MCF-7, and MCF-12A cells in a concentration range of 1-2lM (43)(44)(45). Accordingly, Edsall et al (2004) demonstrated that the same compound inhibited MDA-MB-231 cancer cell proliferation by 50% at 1 lM (30).…”
Section: Docking Results: Caii Versus Caixmentioning
confidence: 99%
“…32 Furthermore, we have previously demonstrated a significant increase in Cdc2 kinase activity in 2-ME-treated cells when compared to vehicle-treated controls in WHCO3 cells. 10 Cdc2 kinase activity was statistically significantly increased (1.7-fold) ( p < 0.005) after 2-ME exposure when compared to vehicle-treated controls. Our observation contributes to the elucidating of the mechanism of action in WHCO3 oesophageal carcinoma cells and reveals that 2-ME causes a metaphase arrest, disrupts mitotic spindle formation, enhances Cdc2 kinase activity leading to persistence of the spindle checkpoint, and thus prolonged metaphase arrest culminating in the induction of apoptosis in WHCO3 cells.…”
mentioning
confidence: 90%
“…The potential role of 2-ME2 as an anti-cancer agent has been intensively investigated. 2-ME2 was found to inhibit growth and induce apoptosis of tumors of Ewing sarcoma [6], chondrosarcoma [7], osteosarcoma [8], esophageal [9], hepatocellular [10], ovarian [11] and nasopharyngeal carcinomas [12], and prostate cancer [13] both in vitro and in vivo. 2-ME2 also showed anti-leukemic activity in vitro with therapeutic selectivity [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…2-ME2 also showed anti-leukemic activity in vitro with therapeutic selectivity [14][15][16]. Several different mechanisms of action have been proposed, including the accumulation of cells in the G 2 /M phase [7][8][9], inhibition of tubule polymerization [17], inhibition of superoxide dismutase (SOD) [14], and accumulation of reactive oxygen species (ROS) [14,15], activation of c-jun N-terminal-activated kinase (JNK) [15], increased expression of p53 and p21 [7,8,10], Bcl-2 phosphorylation [11], and mitochondrial release of cytochrome c [14,15]. However, its exact mechanism on human acute T lymphoblastic leukemia remains unknown.…”
Section: Introductionmentioning
confidence: 99%